Triple site sexually transmitted infection testing as a crucial component of surveillance for men who have sex with men: A prospective cohort study. (February 2022) - Zucker, Roy; Gaisa, Michael; Sigel, Keith; Singer, Ilan; Adler, Amos; Turner, Dan; Ben Ami, Ronen; Nissan, Israel; Chan, Courtney; Halperin, Tamar
Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections are common among men who have sex with men (MSM). Many oropharyngeal and anorectal infections remain asymptomatic. We aimed to evaluate triple-site screening following PrEP introduction. We enrolled a prospective cohort study including 210 asymptomatic MSM during 2019–2020, analyzed by groups: HIV positive (HIV+), HIV−uninfected using PrEP (HIV−/PrEP+), or HIV-uninfected not using PrEP (HIV−/PrEP−). A self-administered questionnaire captured demographic information and sexual risk-taking behaviors. CT/NG testing results were compared between study groups and predictors of infection were evaluated. We included 59 HIV+, 70 HIV−/PrEP+, and 81 HIV−/PrEP− subjects. 30% ( n = 62) of participants tested positive for CT/NG. HIV−/PrEP+ group had highest proportion of infections ( n = 33, 47%) followed by HIV−/PrEP− ( n = 16, 22%) and HIV+ ( n =13, 20%; p < .001). Importantly, 98% (80/82) of pharyngeal/anorectal CT/NG infections were missed in genitourinary tract screening alone. PrEP use and previous syphilis infection were the strongest risk factor for CT/NG. Extra-genital asymptomatic CT/NG infections were prevalent among MSM. These data highlight the importance of routine extra-genital CT/NG testing in asymptomatic sexually active MSM. The study describes the consequences for three-site testing lack of implementation in the PrEP era.